The Influence of Compensation and Work Life Balance on Organizational Commitment with Employee Engagement as a Mediating Variable - Asfiah, Nurul; Anggun Mar’atus Sholiha, Dhiva; Widagdo, Bambang (Business Innovation Management and Entrepreneurship Journal, 2026)
The company is obliged to develop and retain employees because they are an important asset in the company's operational processes so that they can...reliable and have a strong desire to participate in achieving company goals according to the company's vision and mission. Therefore, the company needs to increase employee organizational commitment which can be done by paying attention to the appropriateness of compensation and the existence of work-life balance, therefore this study aims to examine the role of compensation and work-life balance on employee performance with employee engagement as a mediating variable. This study was conducted at PT. Syandana Urban Rekatama involving 140 field employees and those who are married and selected using purposive sampling techniques. Data collection techniques used questionnaires and interviews which were then analyzed using Structural Equation Modeling - Part Least Square (SEM-PLS). The results showed that compensation and work-life balance have a positive and significant effect on organizational commitment. Furthermore, employee engagement is able to mediate the relationship between compensation and work-life balance on organizational commitment. These findings highlight the importance of adjusting compensation and providing employees with work-life balance in order to increase employee engagement and thus increase employee organizational commitment.